The other side of Zen : a social history of Sōtō Zen : Buddhism in Tokugawa Japan - Williams, Duncan Ryūken, 1969- (Buddhisms., 2005)
"Popular understanding of Zen Buddhism typically involves a stereotyped image of isolated individuals in meditation, contemplating nothingness. This book presents the "other side of Zen," by examining the movement's explosive growth during the Tokugawa period (1600-1867) in Japan and by shedding light on the broader Japanese religious landscape during the era. Using newly-discovered manuscripts, Duncan Ryuken Williams argues that the success of Soto Zen was due neither to what is most often associated with the sect, Zen meditation, nor to the teachings of its medieval founder, Dogen, but rather to the social benefits it conveyed." "Williams's work is based on careful examination of archival sources including temple logbooks, prayer and funerary manuals, death registries, miracle tales of popular Buddhist deities, secret initiation papers, villagers' diaries, and fundraising donor lists."--Jacket